PALEOZOIC PLANKTON REVOLUTION: EVIDENCE FROM EARLY GASTROPOD ONTOGENY - Nutzel A.; Fryda J. (My University, 2003)
A major macroevolutionary trend in gastropod larval shell morphology occurred throughout the middle and late Paleozoic. The majority of Ordovician and Silurian gastropods have openly coiled initial whorls; this morphology was gradually lost. Mesozoic gastropods have exclusively tightly coiled initial whorls. Most protoconchs were formed by planktonic larvae, and this is the first documentation of a supraspecific trend in Paleozoic invertebrate larvae. Open coiling makes shells weak and vulnerable to attack and force. The replacement of weak-shelled plankton by stronger-shelled plankton was probably caused by predatory, selective forces. It coincides with other fundamental changes in plankton communities during the middle and late Paleozoic, including the decline of acritarchs and graptolites. Plankton communities suffered from crises that were probably caused by extrinsic forces. During plankton restructuring in the aftermath, predation could have become an increasingly important selective factor for gastropod larvae. [PUBLICATION ABSTRACT]
Keywords: PLANKTON; ALGAE; GEOLOGY; Mesozoic; Silurian; Ordovician; Mesozoic; Paleozoic::Silurian; Мезозой; Палеозой::Ордовикская; Палеозой::Силурийская; Paleozoic::Ordovician